2008
DOI: 10.1093/jac/dkn352
|View full text |Cite
|
Sign up to set email alerts
|

Non-susceptibility trends among Pseudomonas aeruginosa and other non-fermentative Gram-negative bacteria from bacteraemias in the UK and Ireland, 2001-06

Abstract: Most P. aeruginosa from bacteraemias in the UK and Ireland remain relatively susceptible by international standards; in contrast, multiresistance is widespread in Acb, with imipenem non-susceptibility emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 22 publications
3
31
2
Order By: Relevance
“…This result is in agreement with published data from large multi-center collaborations [43,44]. Resistance to standard antipseudomonal agents was observed to increase with increasing contact with the healthcare system.…”
Section: Factorsupporting
confidence: 92%
“…This result is in agreement with published data from large multi-center collaborations [43,44]. Resistance to standard antipseudomonal agents was observed to increase with increasing contact with the healthcare system.…”
Section: Factorsupporting
confidence: 92%
“…Thus, attention should be paid to Acb complex colonization or infection in these cases. Strains of drug- Other investigators showed that bacterial sensitivity to carbapenems has dramatically decreased in recent years (11,18). In contrast, the present study revealed that most of the 201 isolates were sensitive to antibiotics, particularly carbapenems.…”
Section: Discussioncontrasting
confidence: 62%
“…Gram-negative bacterial resistance is of particular importance as there is a dearth of novel antibiotics directed against these organisms (1), which are increasing in prevalence worldwide (8,12,15). Logically, an association should exist between antibiotic consumption and Gram-negative bacterial resistance, and this was demonstrated in multiple studies in both the hospital and community settings (2,7,10,13,18).…”
mentioning
confidence: 99%